2015
DOI: 10.1371/journal.pone.0124461
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Differences in Outcome of Ascending Aortic Aneurysm Surgery

Abstract: ObjectivesGender specific differences receive increasing attention and are known to affect the outcome of cardiovascular diseases. We investigated possible risk-factors for gender-specific differences in ascending aortic aneurysm surgery.Methods548 consecutive patients (male: n = 390, age: 58.3±14.4 years; female: n = 158, age: 65.3±12.9 years) with aneurysms of the ascending aorta eligible for cardiac surgery were retrospectively analyzed.ResultsWomen were significantly older when operation was indicated (p<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 19 publications
3
31
0
2
Order By: Relevance
“…29,30 All aortic dissections occurred in men and male sex is a recognized risk factor for this complication. 31 However, Beller et al 32 did not manage to show any difference in percentage of patients with BAV presenting with dissection according to sex (25.8% versus 20.0%, P=0.4). This is most likely because of referral bias as in their study only patients with aneurysms of the AA eligible for cardiac surgery were retrospectively analyzed.…”
Section: Bav Complications In Men and Womenmentioning
confidence: 90%
See 1 more Smart Citation
“…29,30 All aortic dissections occurred in men and male sex is a recognized risk factor for this complication. 31 However, Beller et al 32 did not manage to show any difference in percentage of patients with BAV presenting with dissection according to sex (25.8% versus 20.0%, P=0.4). This is most likely because of referral bias as in their study only patients with aneurysms of the AA eligible for cardiac surgery were retrospectively analyzed.…”
Section: Bav Complications In Men and Womenmentioning
confidence: 90%
“…This is most likely because of referral bias as in their study only patients with aneurysms of the AA eligible for cardiac surgery were retrospectively analyzed. 32 Nevertheless, the higher frequency of aortic complications among men with BAV compared with women suggests the need of close control of aortic dimensions over time.…”
Section: Bav Complications In Men and Womenmentioning
confidence: 99%
“…1,8 Prior studies have reported differences in cardiovascular disease risk profile between male and female patients, which is thought to greatly contribute to this under-recognition and worse outcomes for female patients. [1][2][3][4][5][6][7] In our cohort, female patients were older with higher rates of pre-existing cerebrovascular disease and previous valve intervention but lower incidence of prior MI than male patients. Older age is particularly consistent with the risk profile of females presenting for cardiac procedures and suggests that female patients may experience a delay in surgical intervention and thus possess more advanced disease at the time of the operation.…”
Section: Discussionmentioning
confidence: 73%
“…Female sex has been found to be related to poorer short-term postsurgical outcomes for many cardiovascular surgical procedures, including aortic surgery, valve replacements, and coronary artery bypass graft (CABG) procedures. [1][2][3][4][5][6] Female patients have often been found to have different preoperative characteristics than males, which may lead to later recognition of disease and delayed surgical intervention. 3,7 Elucidating the different clinical presentation of female patients and outcome differences to allow recognition of these patients pre-operatively could further optimize postoperative management for cardiovascular procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Skýringin er ekki ljós en þetta á baeði við um valaðgerðir og bráðaaðgerðir þegar flysjun verður á ósaeðargúlpi. 18,29,30 Í okkar rannsókn sást þó ekki marktaekur munur á 30 daga dánarhlutfalli karla og kvenna, enda ekki við því að búast þar sem aðeins tveir sjúklingar létust innan 30 daga. Báðir voru konur, sem allt eins gaeti hafa verið tilviljun.…”
Section: Umraeðaunclassified